UJI IMUNOMODULATOR DARI EKSTRAK ETANOL DAUN WARU (HIBISCUS TILIACEUS) DENGAN METODE HIPERSENSITIVITAS TIPE LAMBAT - Yanna Rotua Sihombing; Debi Dinha Octora (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2019)
Immunomodulator is a compound that can increaase the imuno system. One of the plants that have immunomodulator’s activity is Waru Leaf (Hibiscus tiliaceus). the purpose of this research was to test the effect of immunomodulator by extract of Waru Leaf ethanol on rat male. The activity of immunomodulator was determined by using digital pletysmometer by measuring the differences between the last leg swelling’s volume and the first leg swelling’s volume. The treatment group were divided into 5 groups. Each group consistof 5 rats CMC-Na 0,5% (negative control), Stimuno® 32,5 mg/kgBW (positive control), dose of EEDW 50, 100 and 200 mg/kgBW, and bacteria E.coli as antigen. The results slowed that distribution of EEDW dose 200 mg/kgBW can give the effect of immunostimulant by swelling enthancement compared by CMC-Na 0,5 %. EEDW 200 mg/kgBW that have activity comparable with Stimuno® 32,5 mg/kgBW. Thus, it is concluded that of Waru Leaf extract has immunomodulator effects on delayed-type hypersensitivity response of rat male.